Analyzing current carbon capture, utilization and storage (CCUS) research and pilot projects in the European cement sector - Ali Abdelshafy; Grit Walther (The Oxford Institute for Energy Studies, 2023)
Reaching carbon neutrality necessitates radical changes in terms of energy sources and industrial technologies. Some industries such as cement and lime emit significant amounts of process emissions, which will continue to be generated regardless of the type of energy source employed. One way to address such 'hard-to-abate' emissions is by employing carbon capture, utilization and storage (CCUS) technologies. Novel technologies such as CCUS undergoes continuous innovation before reaching high technological maturity and their commercial potential. To that extent, research and pilot projects represent an effective technology-push tool to minimize relevant uncertainties, risks and costs and increase the technology's readiness level. In recent years, different CCUS demonstration projects have been implemented and financed differently. This study investigates the role of these projects in the future deployment of CCUS technologies, with focus on the European cement sector specifically. Overall, the paper aims to evaluate the status quo of decarbonization of the cement sector via CCUS and to discuss the required future activities and measures to enhance the technology's integration into the sector.
Keywords: 330; carbon capture; carbon neutrality; CCS; CCUS; cement sector; decarbonization; energy-intensive industries; hard-to-abate emissions